Safety and Efficacy of Sildenafil for Group 2 Pulmonary Hypertension in Left Heart Failure - Kinjal Desai; Michael Di Lorenzo; Warren A. Zuckerman; Ezinne Emeruwa; Usha S. Krishnan (MDPI AG, 2023)
Pulmonary hypertension (PH) is a multifactorial, progressive disease with poor outcomes. Group 2 PH is defined by pulmonary vascular disease with elevated pulmonary capillary wedge pressure including both left-sided obstructive lesions and diastolic heart failure (HF). Sildenafil was historically discouraged in this population as pulmonary vasodilation can lead to pulmonary edema. However, evidence suggests that sildenafil can help to treat the precapillary component of PH. This is a single center, retrospective pilot study of pediatric PH patients with left-sided HF who were treated with sildenafil for ≥ 4 weeks. HF patients without mechanical support (HF group) and HF patients with a left ventricular assist device (HF-VAD) were analyzed. The exploratory analysis described the safety and side effects of the drug. Echocardiographic parameters were compared before and after sildenafil treatment in a paired analysis. The changes in medical therapy during treatment, mechanical support, and mortality was reported; 19/22 patients tolerated sildenafil. Pulmonary edema in two patients resolved upon discontinuation of sildenafil. In the HF group, both the right atrial volume and right ventricular diastolic area decreased, and the tricuspid regurgitation (TR) S/D ratio decreased after therapy (p = 0.02). Across both the groups, four patients weaned off milrinone and seven weaned off inhaled nitric oxide. Of the thirteen HF patients, four received a transplant, and all of the nine HF-VAD patients received a transplant. Sildenafil can be safely used in carefully selected patients with HF and mixed pre/postcapillary PH with judicious titration and inpatient surveillance, with patients showing improvements in echocardiographic parameters.